KAJIAN INDEKS STANDAR PENCEMAR UDARA (ISPU) KARBON MONOKSIDA (CO) TERHADAP KESEHATAN MASYARAKAT DI KOTA PADANG - Ridia Wahyu; Sanny Edinov; Mistia Sari; Dertha Mukhtar (Smart Education, 2025)
Abstract: This study aims to examine the Carbon Monoxide (CO) Air Pollutant Standard Index (ISPU) and its impact on public health in Padang City. With the increasing number of motorized vehicles and industrial activity, air quality in Padang City has declined, potentially endangering public health. The CO ISPU data was obtained from the Air Quality Monitoring System (AQMS) installed in Padang City during 2024. The results showed that the average CO concentration was in the